Assessing the sewage discharge effects on soft-bottom macrofauna through traits-based approach. (December 2021) - Vesal, Seyed Ehsan; Nasi, Federica; Pazzaglia, Jessica; Ferrante, Larissa; Auriemma, Rocco; Relitti, Federica; Bazzaro, Matteo; Del Negro, Paola
Abstract: We assessed the effect of sewage-derived materials on the structural and functional attributes of the soft-bottom macrofauna at an increasing distance from the entire diffusion area. Our results showed clear spatial changes of macrofaunal density and biomass along the distance gradient from the main outfall. High values of biodiversity, species composition, and species linked to organic enrichment near the duct suggested that moderate organic stress affected this community. The traits analysis abundance-based, compared to biomass-based one, distinguished most clearly sewage contamination conditions. Functional diversity displayed spatial patterns with higher values in the less impacted sites and was significantly related to species numbers and the biotic indices (like M-AMBI). This approach is ideal for detecting macrofaunal functional changes due to sewage contamination. Thus, we infer that traits analyses could offer great potential for environmental assessment and monitoring of coastal areas influenced by human activities. Highlights: Community features were affected by moderate organic stress. Functional diversity displayed higher values in the less impacted sites. Analyses abundance-based distinguished most clearly sewage contamination. Traits analysis is ideal to detect macrofaunal functional changes due to sewage contamination.